Integrating external stakeholders for green innovation in third-party logistics: The mediating role of green absorptive capacity - Bálint, M.; Ferreira, L. M. D. F.; Vilas-Boas da Silva, J. M.; Möhring, M. M. (International Journal of Logistics Management, 2026)
Purpose This study addresses recent calls from scholars to broaden research on the organizational capabilities of logistics firms that facilitate the dynamic interaction between acquiring and utilizing intangible resources for green innovations. It builds on the integrative and organizational learning perspectives of the natural-resource-based view (NRBV) to evaluate how external stakeholder integration (SI) and green absorptive capacity (GAC), two distinct yet complementary strategic capabilities, interact to promote the adoption of green innovations in third-party logistics providers (3PLs). Design/methodology/approach A cross-sectional survey-based approach was adopted. Online questionnaires were distributed to top managers responsible for sustainability at German 3PLs. The collected data were processed using AMOS 26 for confirmatory factor analysis, and hierarchical regression analysis was employed to test the proposed hypotheses. Findings The findings reveal positive full mediation through GAC in the relationship between SI and the adoption of green innovations, with notable variations in mediation effect sizes across different innovation subsets, suggesting the need for context-specific approaches. Originality/value By empirically demonstrating how SI and GAC interact to shape green innovation outcomes, this study offers new insights into the internal organizational capabilities required for greening in 3PL firms. It is among the first to establish the mediating role of GAC on stakeholder-driven innovation in logistics, thus extending the green logistics literature and providing guidance for 3PL managers seeking a competitive edge through environmental sustainability.